2021
DOI: 10.3390/su13169082
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Analysis of Students’ Reflections on the Current Use of Digital Media in Foreign Language Classes

Abstract: Teaching and learning have radically changed in the COVID-19 era and highlighted many novel aspects of online teaching and learning. Based on a qualitative content analysis of central European university students’ responses, the aim of this study is to discuss their reflections on the use of digital media in foreign language classes during the COVID-19 pandemic. The key method of this qualitative study includes focus group interviews. The results reveal both advantages and disadvantages of online foreign langu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…The justification for choosing the focus group discussions approach was to highlight the differences in perspective between groups of individuals as well as provide information about a range of ideas and feelings that individuals have about certain issues (Klimova, Pikhart, Cierniak-Emerych, & Dziuba, 2021). The questions of this focus group were shaped based on the research objectives.…”
Section: Methodsmentioning
confidence: 99%
“…The justification for choosing the focus group discussions approach was to highlight the differences in perspective between groups of individuals as well as provide information about a range of ideas and feelings that individuals have about certain issues (Klimova, Pikhart, Cierniak-Emerych, & Dziuba, 2021). The questions of this focus group were shaped based on the research objectives.…”
Section: Methodsmentioning
confidence: 99%
“…To enhance comprehension of the Covid-19 situation and bolster the theoretical and methodological aspects of the study, we extensively analysed and collected secondary material from many sources like books, scholarly articles, company reports, and web resources. The main data is collected by qualitative interviews and open-ended inquiries with students (Klimova et al, 2021).The data was individually obtained from the research participants. The researcher personally gathered the appropriate data by directly interacting with the research subjects.…”
Section: Data Collectionmentioning
confidence: 99%
“…This ability to manage communication is important for the success of distance learning, as the researchers pointed toward collaboration, enabled by communication, as enabling or hindering students' building of knowledge. Klimova et al [48] reported that the lack of social contact-which included the absence of collaboration between the teacher and students, and between the students themselves-resulted in little sharing and building of knowledge and experience by the students.…”
Section: Communicational Processesmentioning
confidence: 99%